Peran Vermikompos terhadap Morfofisiologi Kangkung Hidroganik - A. R. Darmawan Putra; Siti Asmaniyah Mardiyani; Nurhidayati Nurhidayati (Agrotechnology Research Journal, 2020)
Since open-field agriculture will face some severe problems in the near future like availability of land and agricultural productivity, an alternative cultivation system, such as soilless cultivation is needed for the sustainability of supply and demand for healthier and safer food. This study aimed to test the effect of vermicompost application method and dosage on growth, yield, and chlorophyll content of water spinach. This experiment used a factorial randomized block design with controls. The first factor was the vermicompost application method, which consisted of three levels, namely solid vermicompost, the combination of solid and liquid vermicompost, liquid vermicompost. The second factor was the vermicompost dosage, which consisted of five levels: 100, 200, 300, 400, and 500g per polybag, compared with control using inorganic fertilizer. The results showed that the vermicompost application method did not significantly affect plant growth and yield. The dosage of 500g in the three different application methods gave significantly higher plant growth compared to control. The fresh weight of water spinach per plant and per polybag in the dosage of 500g showed the highest yield of 13.95g and 122.17g, respectively. The highest chlorophyll content of water spinach was found in solid vermicompost treatment with an application rate of 500g, namely 30.10 µg/ml (chlorophyll A) and 54.79 µg/ml (chlorophyll B). These results indicate that to produce high-quality water spinach in soilless culture systems, it is recommended to use solid vermicompost with an application rate of 500g per polybag.